2022
DOI: 10.3390/nu14173471
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adherence to the Mediterranean Diet and Anthropometric and Health Variables in College-Aged Males

Abstract: The present study aimed to verify the association between adherence to the Mediterranean diet (MD) and anthropometric and health variables. Four-hundred-and-ninety-five college-aged males aged 18–25 participated in this cross-sectional research. The KIMED (Mediterranean Diet Quality Index for children and adolescents) was used to assess the adherence to MD. The following variables were also assessed: body mass (BM), height (HE), body mass index (BMI), body fat percentage (%FAT), lean mass (LEAN), abdominal gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, in contrast to us, they also found the association of the MDS with all adiposity measures except waist to hip ratio. In the same direction, Prieto-González et al reported correlations between better adherence to the Mediterranean diet and lower BMI and body fat in college males and a very weak correlation with waist to hip ratio 22 . Consistent with our findings, waist-related variables such as waist circumference and waist to height ratio have been the only anthropometric measures which inversely associated with adherence to the Mediterranean diet in some investigations 23 25 but there are also studies in which no association was found with measures of general or abdominal obesity or body fat 13 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, in contrast to us, they also found the association of the MDS with all adiposity measures except waist to hip ratio. In the same direction, Prieto-González et al reported correlations between better adherence to the Mediterranean diet and lower BMI and body fat in college males and a very weak correlation with waist to hip ratio 22 . Consistent with our findings, waist-related variables such as waist circumference and waist to height ratio have been the only anthropometric measures which inversely associated with adherence to the Mediterranean diet in some investigations 23 25 but there are also studies in which no association was found with measures of general or abdominal obesity or body fat 13 .…”
Section: Discussionmentioning
confidence: 83%
“…Similar to other cardiometabolic risk factors, the relationship of blood glucose and the Mediterranean dietary pattern is controversial and both cases of an inverse 22 , 26 , 27 or no 26 , 28 , 29 relationship have been reported. The same scenario exists for HDL cholesterol as there are reports on both positive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Decreased adherence to the MD has resulted in adopting dietary patterns less conducive to optimal health, leading to a decline in nutritional quality. 61 , 62 In a population-based and observational study in Greece, adhering to the MD may have a protective effect against childhood overweight or obesity. 63 Research indicates a positive association between physical activity and other health-promoting behaviors, such as appropriate dietary intake and adherence to MD, among children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The authors point out the importance of carrying out further research that contemplates people with pathologies in order to provide an answer to the unknown. However, it is to be expected that in the population with CVD, cancer and other chronic NCDs, a change in dietary pattern will occur after their detection and diagnosis, since diet plays a very important role in the prevention of these pathologies, and specifically the MD is referenced in many medical guides as a recommended dietary pattern [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%